Two ramp reference voltages CDS scheme applied to low noise and high dynamic range PWM pixel. (May 2023) - Gao, Jing; Yang, Xin; Shi, Xiaopei; Gao, Zhiyuan; Nie, Kaiming; Xu, Jiangtao
Abstract: To achieve noise elimination and dynamic range extension in pulse width modulation (PWM) pixels, this paper proposes the new correlated double sampling (CDS) scheme. The proposed CDS scheme uses two ramp reference voltages instead of one two-stage ramp reference voltage. Two reference voltages are both ramp voltages to detect low illumination. Compared to traditional CDS that uses one two-stage ramp reference voltage, proposed CDS guarantees two crosses between photodiode voltage and reference voltages in high illumination. The simulation shows that the maximum photocurrent with proposed CDS is always larger than 10 nA while the maximum photocurrent with traditional CDS is always less than 495 pA at an exposure time of 1 ms and an 8-bit counter. For the PWM pixel adopting proposed CDS, offset of the comparator after CDS operation is 980.479 μV which is reduced by 93.8%, and reset noise of the reset transistor after CDS operation is 11.963 μV which is reduced by 97.1%.